Establishment survival in East and West Germany: A comparative analysis - Daniel Fackler (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2014)
Using a large administrative dataset and methods of survival analysis, I analyze for the period 1994-2008 whether new establishments' survival chances differ between East and West Germany and whether they converged over time. I find that new establishments in East Germany had relatively good survival chances between 1994 and 1997, with no big differences between East and West Germany. In 1998 and 1999 the exit hazard increased strongly in East but not in West Germany, which is likely to be due to a change in the subsidy policy affecting East Germany. Since 2000 the difference in establishments' exit hazard between East and West Germany has become smaller and towards the end of the observation period it is not statistically significant anymore. – – Anhand umfangreicher administrativer Daten untersucht diese Studie für die Jahre 1994 bis 2008 mit Methoden der Verweildaueranalyse, ob sich die Überlebenschancen neu gegründeter Betriebe zwischen West- und Ostdeutschland unterscheiden und ob sie sich im Zeitablauf angenähert haben. Die Ergebnisse zeigen, dass Betriebe in Ostdeutschland von 1994 bis 1997 relativ gute Überlebenschancen aufweisen, die sich kaum von denen westdeutscher Betriebe unterscheiden. In den Jahren 1998 und 1999 steigt die Schließungswahrscheinlichkeit in Ostdeutschland stark an, in Westdeutschland jedoch nicht, was vermutlich auf eine Änderung der Subventionspolitik für Betriebe in Ostdeutschland zurückzuführen ist. Seit dem Jahr 2000 haben sich die Schließungswahrscheinlichkeiten von Betrieben in West- und Ostdeutschland angenähert und unterscheiden sich gegen Ende des Beobachtungszeitraums nicht mehr signifikant voneinander.
Keywords: L2; D22; M13; P27; C41; 330; startups; firm exits; East Germany